THE CONDITION OF CORONARY ARTERIES AND ENDOVASCULAR TREATMENT OUTCOMES IN YOUNG PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - Zeynalov, R.V.; Isaev, E.I.; Abbasov, E.F.; Samadov, F.M.; Aliyev, F.V. (World of Medicine and Biology, 2015)
The urgency of the problem of acute myocardial infarction and coronary atherosclerosis in young age to date is confirmed by the increased mortality and disability in young people with coronary heart disease and the incidence of atherosclerotic process among them (77%). According to the epidemiological data, major risk factors for coronary heart disease are family history (50%), nephrotic syndrome, familial hypercholesterolemia, smoking, hyperlipidemia, diabetes, hypertension, hyperhomocysteinemia, antiphospholipid syndrome, which suggests a genetic predisposition. As a rule, the heart attack at young people is preceded for the first time with the cardiac angina (24%), less than a week, with the defeat of the lower wall of the left ventricle (43%) and the development of acute cardiac insufficiency (41%). Cases of supraventricular arrhythmias were observed in 11%, atrial fibrillation in 5%, ventricular tachycardia in 30% of young patients. Analysis of laboratory data revealed a significant increase in the level of creatine phosphokinase (CPK), leukocytes, troponin. The single vessel disease or absence of vascular lesions is being diagnosed more often by coronary angiography. The frequency of two-vessel disease was the same as in the elderly, and the presence of three-vessel disease less than it was in a young group. Revascularization was successful (93%) had a favorable forecast and a little complications. The aortocoronary bypass surgery needed only in 5% of cases after endovascular procedures. The survival rate was 92%. The use of thrombolytic medication is recognized as an effective treatment for young patients as thrombosis of the coronary arteries are detected more frequently than older people. Administration of beta adrenergic blockers should be postponed in young patients, as it is in spasm of the coronary arteries helps to promote alpha adrenoceptor. Administration of nitrate is also compulsory in young patients undergoing myocardial infarction.